Holistic care model of time-sharing management for severe and critical COVID-19 patients - Yang, Bo (World J Clin Cases, 2020)
The rapid global outbreak of coronavirus disease 2019 (COVID-19) and the surge of infected patients have led to the verge of exhaustion of critical care medicine resources worldwide, especially with regard to critical care staff. A holistic care model on time-sharing management for severe and critical COVID-19 patients is proposed, which includes formulation of individualized care objectives and plans, identification of care tasks in each shift and making detailed checklist, and management of quality of care. This study was conducted in the COVID-19 treatment center of Harbin, Heilongjiang Province. The data collected from the treatment center were recorded and analyzed. From the results we can deduce that it is especially suitable for non-intensive care unit (non-ICU) nurses to adapt care management mode of ICU as soon as possible and ensure the quality and efficiency of care during the epidemic. The holistic care model on time-sharing management for severe and critical cases with COVID-19 proposed based on our daily work experiences can assist in improving the quality and efficiency of care, thus reducing the mortality rate of patients in ICU.